Electronic Banking and the Financial Performance of Commercial Banks - Mathenge, Claudia Wabera (University of Embu, 2020)
The banking industry has experienced notable transformation especially through technology and innovation. Most banks have adopted E-banking services which have been convenient to customers in accessing financial services. It is from this influence that this study seeks to determine the effects of electronic banking on the financial performance of commercial banks. This study established how the independent variable, that is investment in electronic banking products, relates to the dependent variables, banks performance measured by return on assets and return on equity. The research reviewed various theories and empirical studies that relate to E-banking and financial performance. These theories include Technology Acceptance Theory, Theory of Planned Behaviour and Theory of reasoned Action. The study population was 42 commercial banks of Kenya. The study used secondary data from Annual Supervision Reports published by the CBK. The data collected relate to the variables used in the study which include Number of Mobile Transactions, Number of cards and Number of ATMs for E-banking, and ROA and ROE for financial performance. Data analysis was done using Microsoft Excel 2016 where multiple regression analysis was obtained to establish the effect of E-banking on financial performance. The study findings showed that E-banking has a positive relationship with financial performance of commercial banks. However, the relationship between mobile transactions and financial performance was negative. This can be attributed to the low penetration of mobile banking by banks compared to service providers like Safaricom. This study recommends banks to innovate cost effective operations. It also recommends to the government to make favourable regulations to E-banking products.